The Design of An Inclusion Dispositive for Great Apes: The Case of the Orangutan Sandra and the Chimpanzee Cecilia in Argentina - Carman, María (2024)
The lawsuits involving great apes focus on one of the perspectives of ethics and animal law: The consideration of animals as subjects of law. Based on the lawsuits involving the orangutan Sandra and the chimpanzee Cecilia, who were confined in zoos in Argentina, we will analyze the inclusion dispositive that materializes their conversion from objects to subjects. To what extent does the anthropocentric conception of animals lose importance in relation to new classificatory judgments, at least in some public forums and with certain species? Our assumption is that a number of elements and technologies (legal statements of legal actions and sentences; public hearings; improvements of the zoo enclosure, medical studies and transfer of animals to a sanctuary) form a dispositive for the expansion of rights that allows a policy of reparation of animals considered similar to us or unjustly mistreated, with risk of life or other objectifiable suffering. From an interdisciplinary perspective between anthropology and law, we first present the arguments used in the lawsuits. Then, we analyze the sentences that led to the release of both primates. And, in the last sections, we reflect on the functioning of these techniques of animal/human rapprochement that seek the inclusion of certain animals in a certain moral community.